Digital technology for quality management in construction: A review and future research directions. (December 2022) - Luo, Hanbin; Lin, Ling; Chen, Ke; Antwi-Afari, Maxwell Fordjour; Chen, Lijuan
Abstract: Significant developments in digital technologies can potentially provide managers and engineers with the ability to improve the quality of the construction industry. Acknowledging the current and future use of digital technologies in construction quality management (CQM), we address the following research question: What developments in digital technologies can be used to improve quality in the construction industry ? In addressing this research question, a systematic review approach is used to examine the studies that have been used for the management of quality in the construction industry. This review indicates that there is a need for digital technology-based quality management to be: (1) enhance defect management for concealed work, (2) enhance pre-construction defects prevention as well as post-completion product function testing, and (3) research on construction compliance inspection as a direction. We suggest that future research focus on quality culture development, advanced data analytics, and behavioral quality assessment. Highlights: Digital technologies for construction quality management are an emerging application field. Quality defect identification and dimensional deviation on concrete and reinforcement inspection were most studied. Numerous studies focused on the evaluation and measurement of apparent quality but lack attention to concealed works. Lack of research on workers' operation onsite for automatically compliance check during the construction process.